Viral Vector Vaccines Against ASF: Problems and Prospectives - Ravilov, Rustam Kh.; Rizvanov, Albert A.; Mingaleev, Danil N.; Galeeva, Antonina G.; Zakirova, Elena Yu.; Shuralev, Eduard A.; Rutland, Catrin S.; Khammadov, Nail I.; Efimova, Marina A. (Frontiers in Veterinary Science, 2022)
African swine fever (ASF) is a highly contagious viral disease affecting pigs, with mortality rates primary foci reaching 100%. The widespread and colossal economic losses from ASF have impacts on the development of animal husbandry practices in most countries in Africa, Asia and Europe. Currently, various approaches towards the development of vaccines against ASF are being employed. A promising new concept centred around more economical and time-consuming vaccine production is based on the use of viral vectors to deliver the selected immunogens. This review discusses the results obtained from testing various viral vectors as carriers of targeted ASF virus genes. The safety and prospects of viral vectors, the possibilities around modulating cellular and humoral immune responses by choosing genes expressing immunodominant antigens, and the degree of protection in experimental animals from infection with a lethal dose of virulent ASF virus strains have been shown.